Criminality: illegal logging of woods in Nigeria’s criminality: illegal Logging of woods in Nigeria’s (2016)
The problems facing the rich forest belts in Nigeria have become so intense in relation to the unemployment dilemma ravaging most youths in several urban and rural settlements as well as the wide-ranging negative impacts on environmental crime in South-West Nigeria. This study examines the dynamics of forest exploitation, youth adaptability and survival strategies in the nation’s forest belt. Data collected for the study was basically qualitative, among a hundred and twenty-five (125) respondents in Ondo-Edo forest belts. It was discovered that a strong network of syndicates often (local and foreign) capitalized on the prevailing surge of unemployment in the country to lure young, unemployed and able-bodied men and women into criminal survival strategies and environmental crime of illegal logging of precious woods (Iroko, Mahogany and Obeche). The study concludes that illegal activities of unemployed youths should be curtailed by providing agro based industries in the forest belt as well as adequate security to stop the illegal and indiscriminate logging of woods by local and foreign syndicates.